Strategi Personal Branding Melalui Digital Marketing Pada Aplikasi TikTok (Studi Kasus Content Creator Reizuka Ari) - Siregar, Efrida Rahma Sari; Atika, Atika; Rahmani, Nur Ahmadi Bi (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
The development of digital technology has significantly influenced marketing strategies, including the use of social media like TikTok for building personal branding. However, research exploring content creators' personal branding strategies remains limited. This study aims to explore the personal branding strategies implemented by Reizuka Ari on TikTok through a digital marketing approach. This research used a descriptive qualitative method with a case study approach. The subject was Reizuka Ari, an active TikTok content creator. Data were collected through content observation and documentation and analyzed using the Authentic Personal Branding theory by Hubert K. Rampersad. The results show that Reizuka Ari successfully builds an authentic personal image through consistent content focusing on skincare, daily life, travel, and food by showcasing his personality in every post. This study contributes to content creators and digital marketing practitioners in developing a strong, consistent, and character-driven identity on video-based social media platforms